Green & deadly things - Lyons, Jenn, 1970- (Tor, 2026)
"Centuries ago, necromancy almost destroyed the world. That's how history remembers it. History remembers it wrong. Mathaiik has trained all his life to join the sacred order of the Idallik Knights, charged with defending their world from the forces of necromancy. Only vestiges of that cursed magic remain, nothing like the fabled days of the Grim Lords, the undead wizards who once nearly destroyed the world. But when an even stranger kind of monster begins to wake, the Knights quickly prove powerless to stop them. Whole forests are coming alive and devouring anyone so foolish as to trespass, as if the land itself has turned upon humanity. It's a good thing, then, that the Grim Lords were never truly destroyed. One of their number sleeps below the Knights' very fortress. And when an army of twisted tree monsters attacks the young initiates in his charge, Math decides to do the unthinkable: he wakes her up. This is only the beginning of his problems. Because said necromancer, Kaiataris, knows something history has forgotten. The threat of this wild magic is part of a cycle that has repeated countless times-life after death, chaos after order. And if she and Math can't find a new way to balance the scales, this won't just be the end of the world as they know it, but the end of all life, everywhere"-- Provided by publisher.